Training-of-trainers gender-workshop in Nepal - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
The CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS) South Asia and the the Youth and Youth and Small Entrepreneur Self-Employment Fund (YSEF), Ministry of Finance, Government of Nepal jointly organised a training-of-trainers workshop for women cooperative members on Gender and Climate Change, in Nepal in July 2013